2021
DOI: 10.3390/vaccines10010012
|View full text |Cite
|
Sign up to set email alerts
|

Pfizer-BioNTech COVID-19 Vaccine in Gynecologic Oncology Patients: A Prospective Cohort Study

Abstract: Objective: To evaluate the safety and immunogenicity of the Pfizer-BioNTech COVID-19 vaccine in gynecologic oncology patients under chemotherapy. Methods: A prospective cohort study including gynecologic oncology women who were under chemotherapy or had completed it within 6 months at the time of the study. All patients received a two-dose schedule of the Pfizer-BioNTech COVID-19 vaccine. Results were compared with a control group of healthy women vaccinated in the same period. Results: Overall, 44 oncologic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a clinical trial, approximately 50 patients with a gynecological cancer diagnosis and who were receiving chemotherapy were evaluated. The authors of the study suggested that protection against Covid‐19 could be achieved with further early booster vaccine doses 14 . In another trial, it was reported that more than two doses of COVID‐19 vaccines might boost immune response, especially in the immunocompromised population or individuals who had comorbidities or increased Covid‐19 exposure risk 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical trial, approximately 50 patients with a gynecological cancer diagnosis and who were receiving chemotherapy were evaluated. The authors of the study suggested that protection against Covid‐19 could be achieved with further early booster vaccine doses 14 . In another trial, it was reported that more than two doses of COVID‐19 vaccines might boost immune response, especially in the immunocompromised population or individuals who had comorbidities or increased Covid‐19 exposure risk 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study suggested that protection against Covid‐19 could be achieved with further early booster vaccine doses. 14 In another trial, it was reported that more than two doses of COVID‐19 vaccines might boost immune response, especially in the immunocompromised population or individuals who had comorbidities or increased Covid‐19 exposure risk. 15 Booster doses for BNT162b2 (Pfizer–BioNTech) and Moderna vaccines is recommended a minimum of 6 months from completion of initial vaccination for risky population, including individuals older than 65 years old, who live in long‐term care facilities, have comorbidities, or have jobs or live in environments with high‐risk for Covid‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In general, some studies reported lower immunogenicity in the cancer patients as compared to healthy controls. For example, Palaia et al, reported that there was no significant difference in the mean antibody titer one month after the second dose of Pfizer vaccination in 44 cancer patients as compared to the controls [ 10 ]. However, a significantly lower titer was reported three months after the second dose in cancer patients as compared to the healthy controls.…”
Section: Immunogenicity Of the Covid-19 Vaccines In Solid And Hematol...mentioning
confidence: 99%
“…Similar results were obtained by Funakoshi et al, who reported significantly lower median antibody titer for the 24 cancer patients receiving chemotherapy (0.161, 95% confidence interval (CI) [0.07–0.857]) after the second dose of the Pfizer vaccine as compared to 12 healthy controls (0.644, 95% CI [0.259–1.498]) ( p < 0.0001) [ 29 ]. Likewise, Palaia et al, found that cancer patients who were receiving active chemotherapy treatment had lower median antibody titer one month and three months after the second dose as compared to those who were not receiving active chemotherapy [ 10 ]. Interestingly, the specific effect of the chemotherapy treatment and its extent varies depending on the drug at hand.…”
Section: Immunogenicity Of the Covid-19 Vaccines In Solid And Hematol...mentioning
confidence: 99%